An Early‐Stage Atherosclerosis Research Model Based on Microfluidics. Issue 15 (17th February 2016) - Zheng, Wenfu; Huang, Rong; Jiang, Bo; Zhao, Yuyun; Zhang, Wei; Jiang, Xingyu
Abstract : The arterial microenvironment plays a vital role in the pathology of atherosclerosis (AS). However, the interplay between the arterial microenvironment and atherogenesis remains unclear, partially due to the gap between cell culture and animal experiments. Addressing this problem, the present study reports a microfluidic AS model reconstituting early‐stage AS. Physiological or AS‐prone hemodynamic conditions are recapitulated on the model. The on‐chip model recaptures the atherogenic responses of endothelial cells (ECs) in ways that the Petri dish could not. Significant cytotoxicity of a clinical anti‐atherosclerotic drug probucol is discovered on the model, which does not appear on Petri dish but is supported by previous clinical evidence. Moreover, the anti‐AS efficiency of platinum‐nanoparticles (Pt‐NPs) on the model shows excellent consistency with animal experiments. The early‐stage AS model shows an excellent connection between Petri dish and animal experiments and highlights its promising role in bridging fundamental AS research, drug screening, and clinical trials. Abstract : An early‐stage atherosclerosis (AS) research model based on a microfluidic chip is reported. AS‐prone hemodynamic conditions are recapitulated on the model, which recaptures the atherogenic responses of endothelial cells that could not be realized on a Petri dish. The early‐stage AS model shows an excellent connection between the Petri dish and animal experiments and highlights its promising role in bridging fundamental AS research, drug screening, and clinical trials.